A wash out on the line. (1928)
1 photograph : sepia toned 8 x 13.5 cm Clothes hanging on the line to dry. Title from album caption. Good An album containing 323 black and white photographs and 25 pages of text, covering the years 1914 to 1937 of the FOMOWA Fishing Club on the Grand Codroy River on the west coast of Newfoundland. The album's images have been digitized as separate items.